Essentials of computing systems - 2ª edição - Fernandes, João M. (2022)
Computers were originally invented to solve all sort of mathematical problems. Nowadays, computers do much more than that and are present in all human activities. In fact, a computer is a fantastic machine capable of doing the most amazing tasks, if an appropriate program is provided. A computer system contains hardware and system software that work together to run software applications. Interestingly, the underlying concepts that support the construction of a computer are relatively stable. In fact, (almost) all computer systems have a similar organisation, i.e., their hardware and software components are arranged in hierarchical layers and perform similar functions. This book was written for programmers and software engineers who want to comprehend how the components of a computer work and how they affect the correctness and performance of their programs.